Optimalisasi Peran Kelelawar Microchiroptera sebagai Biokontrol Serangga Tomcat (Paederus fuscipes) dan Ulat Bulu (Lymantriidae) di Perkotaan - Fahma Wijayanti (Al-Kauniyah: Jurnal Biologi, 2013)
The research aims to determine the diet of microchiroptera bats in   urban areas..  The research was done in June 2012 to August 2012. Sample of bat was captured in six locations using misnet and harp net at bat foraging areas.  Stomach contents was collected and dissolved in aquadest. The material of insect were sorted and identified under microscope and compare to the insects that were collected by light trap in bat foraging area. The data were analyzed by Principle Component Analysis (PCA). There were three species of insectivorous bat which catch at South Tangerang and South Jakarta. The insects in gut content of insectivorous bats belong to 8 orders, distributed into 12 families. Based on prey preference, the insectivorous bats can be classified into two groups.  This study proves that the tomcat beetles eaten by Hipposideros sp. and Chaerophon plicata, while Lymantriidae moth being eaten by Hipposideros sp. and  Murina sp.